Who am I? An identity crisis Identity in the new museologies and the role of the museum professional (Cadernos de Sociomuseologia, 2010)
Whilst the title of this essay suggests more than one “new museology”, it was rather a licence poétique to emphasize the two major theoretical movements that have evolved in the second half of the 20th Century[1]. As a result of the place(s)/contexts where they originated, and for clarity purposes, they have been labelled in this essay as the “Latin new museology” and the “Anglo-Saxon new museology”; however they both identify themselves by just the name of “New Museology”. Even though they both shared similar ideas on participation and inclusion, the language barriers were probably the cause for many ideas not to be fully shared by both groups.   The “Latin New museology” was the outcome of a specific context that started in the 1960s (de Varine 1996); being a product of the “Second Museum Revolution”(1970s)[2], it provided new perceptions of heritage, such as “common heritage”. In 1972 ICOM organized the Santiago Round Table, which advocated for museums to engage with the communities they serve, assigning them a role of “problem solvers” within the community (Primo 1999:66). These ideas lead to the concept of the Integral Museum. The Quebec Declaration in 1984 declared that a museum’s aim should be community development and not only “the preservation of past civilisations’ material artefacts”, followed by the Oaxtepec Declaration that claimed for the relationship between territory-heritage-community to be indissoluble (Primo 1999: 69). Finally, in 1992, the Caracas Declaration argued for the museum to “take the responsibility as a social manager reflecting the community’s interests”(Primo 1999: 71). [1] There have been at least three different applications of the term ( Peter van Mensch cited in Mason: 23) [2] According to Santos Primo, this Second Museum Revolution was the result of the Santiago Round Table in Chile, 1972, and furthered by the 1st New Museology International Workshop (Quebec, 1984), Oaxtepec Meeting (Mexico, 1984) and the Caracas Meeting (Venezuela, 1992) (Santos Primo : 63-64)